PENGARUH PEMBERIAN PUPUK KOTORAN AYAM DAN BURUNG PUYUH PADA MEDIA KULTUR DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN POPULASI Daphnia sp. - Ibnu Hasani; M Bahrus Syakirin; Tri Yusufi Mardiana (Fakultas Perikanan Universitas Pekalongan, 2017)
The aim of research is to determine the optimal dose of fertilizer so that it can produce the maximum population growth. This research using Complete Random Design (RAL) method with 4 treatments and 3 repetitions. As the treatment is a dose of chicken manure (25%) and quail (75%), the dose oftreatment A 0 gr/L, treatment B 2 gr/L, treatment C 4 gr/L and D treatment 6 gr/L. Based on the results of the experiment, treatment D showed the highest results (1188,33 Ind/L), then followed by treatment C (10440,00 Ind/L), treatment B (9216,67 Ind/L) and treatment A (5440,00 Ind/L), while the responseof the population growth of Daphnia sp. to doses of chicken and quail manure in a culture media showedpolinier with the equation Y = 5939.33 + 1055.5 X (R2 = 0.96). TheCondition of water qualityduring a research is still apropiate for supporting life and population growth of Daphnia sp.The temperature during the research was 26-28,5C, DO was 2,4-3,8 mg / l, and pH was 6, 5-8, 9.Keywords: Daphnia Sp, Culture, Chicken manure, quail manure, water quality.